Proceedings of the First International Conference on Stepped Wedge Trial Design. Issue 1 (July 2016) - Kanaan, Mona; Mdege, Noreen; Keding, Ada; Parker, RA; Mills, N.; Shah, A.; Strachan, F.; Keerie, C.; Weir, C.; Forbes, Andrew; Hemming, Karla; Lawton, Sarah; et al.
Table of contents I1 Introduction Mona Kanaan, Noreen Dadirai Mdege, Ada Keding O1 The HiSTORIC trial: a hybrid before-and-after and stepped wedge design RA Parker, N Mills, A Shah, F Strachan, C Keerie, CJ Weir O2 Stepped wedge trials with non-uniform correlation structure Andrew Forbes, Karla Hemming O3 Challenges and solutions for the operationalisation of the ENHANCE study: a pilot stepped wedge trial within a general practice setting Sarah A Lawton, Emma Healey, Martyn Lewis, Elaine Nicholls, Clare Jinks, Valerie Tan, Andrew Finney, Christian D Mallen, on behalf of the ENHANCE Study Team O4 Early lessons from the implementation of a stepped wedge trial design investigating the effectiveness of a training intervention in busy health care settings: the Thistle study Erik Lenguerrand, Graeme MacLennan, John Norrie, Siladitya Bhattacharya, Tim Draycott, on behalf of the Thistle group O5 Sample size calculation for longitudinal cluster randomised trials: a unified framework for closed cohort and repeated cross-section designs Richard Hooper, Steven Teerenstra, Esther de Hoop, Sandra Eldridge O6 Restricted randomisation schemes for stepped-wedge studies with a cluster-level covariate Alan Girling, Monica Taljaard O7 A flexible modelling of the time trend for the analysis of stepped wedge trials: results of a simulation study Gian Luca Di Tanna, Antonio Gasparrini P1 Tackling acute kidney injury – a UK stepped wedge clinical trial of hospital-level quality improvement interventions Anna Casula, Fergus Caskey, Erik Lenguerrand, Shona Methven, Stephanie MacNeill, Margaret May, Nicholas Selby P2 Sample size considerations for quantifying secondary bacterial transmission in a stepped wedge trial of influenza vaccine Leon Danon, Hannah Christensen, Adam Finn, Margaret May P3 Sample size calculation for time-to-event data in stepped wedge cluster randomised trials Fumihito Takanashi, Ada Keding, Simon Crouch, Mona Kanaan P4 Sample size calculations for stepped-wedge cluster randomised trials with unequal cluster sizes Caroline A. Kristunas, Karen L. Smith, Laura J. Gray P5 The design of stepped wedge trials with unequal cluster sizes John N.S. Matthews P6 Promoting Recruitment using Information Management Efficiently (PRIME): a stepped wedge SWAT (study-within-a-trial) R Al-Shahi Salman, RA Parker, A Maxwell, M Dennis, A Rudd, CJ Weir P7 Implications of misspecified mixed effect models in stepped wedge trial analysis: how wrong can it be? Jennifer A Thompson, Katherine L Fielding, Calum Davey, Alexander M Aiken, James R Hargreaves, Richard J Hayes S1 Stepped Wedge Designs with Multiple Interventions Vivian H Lyons, Lingyu Li, James Hughes, Ali Rowhani-Rahbar S2 Analysis of the cross-sectional stepped wedge cluster randomised trial Karla Hemming, Monica Taljaard, Andrew Forbes